35 Mentoring medical students towards oncology: results from a pilot multi-institutional mentorship programme. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rallis, Kathrine S; Wozniak, Anna Maria; Hui, Sara; Stammer, Adam; Cinar, Cigdem; Sun, Min; Fulton-Ward, Taylor; Clarke, Alison A; Papagrigoriadis, Savvas; Papalois, Apostolos; Sideris, Michail
Abstract : Background: The mounting global cancer burden has generated an increasing demand for oncologists to join the workforce. Yet, students report limited oncology exposure in undergraduate medical curricula, while undergraduate oncology mentorships remain underutilised. We established an undergraduate oncology society-led mentorship programme aimed at medical students across several United Kingdom universities to increase medical student oncology exposure. Methods: We electronically recruited and paired oncologist mentors and medical student mentees and distributed a dedicated questionnaire (pre and post-mentorship) to compare mentees' self-reported cancer specialty knowledge and oncology career motivation after undertaking a 6-week mentorship. We also determined students' interest across specialties and subspecialties and measured mentor availability via percentage programme uptake. Statistical analysis included univariate inferential tests on SPSS software. Results: Twenty-nine (23.4%) of 124 oncology specialists agreed to become mentors. The mentorship was completed by 30 students across 3 medical schools: 16 (53.3%) Barts, 10 (33.3%) Birmingham, and 4 (13.3%) King's; 11 (36.7%) mentored by medical oncologists, 10 (33.3%) by clinical/radiation oncologists, and 9 (30%) by surgical oncologists. The mentorship generated a statically significant increase in students' knowledge of the multidisciplinary team (p<0.001) as well as the role of medical (p<0.001), surgical (p=0.006), and clinical oncologists (p<0.001) and their involvement in academia/research (p=0.001). Mentees' interest in oncology remained unchanged. Further feedback demonstrated that 93.3% of mentees believed that the mentorship scheme made them a better medical student or a future doctor. Additionally, 96.7% of students reported that they would chose to take part in the programme again. Conclusion: Undergraduate oncology mentoring is an effective educational, networking and motivational tool for medical students. Student societies are a valuable asset in cultivating medical student oncology interest by connecting students to faculty and increasing mentor accessibility. Further research should focus on developing an optimal mentorship structure and evaluating long-term outcomes of such educational initiatives.